PENGARUH MOTIVASI, EFIKASI DIRI DAN DISIPLIN KERJA TERHADAP KINERJA GURU PADA SMP NEGERI 7 DENPASAR - Ni Made Satya Utami; Ni Putu Ayu Sintya Saraswati; Ni Kadek Ayu Martini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Maximizing human resources is the main focus in institutions generally in improving teacher performance. Teacher performance is influenced by many factors such as motivation, self-efficacy and work discipline. This research aims to determine the influence of work motivation, self-efficacy and work discipline on teacher performance. The location of this research is at SMP Negeri 7 Denpasar. The population used teachers at SMP Negeri 7 Denpasar and a sample of 50 teachers. Data analysis techniques use Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Determination Coefficient, F Test and t Test. From the research results, it was found that work motivation had a positive and significant effect on teacher performance, self-efficacy had a positive and significant effect on teacher performance, and work discipline had a positive and significant effect on teacher performance. Suggestions that can be given by researchers are that teachers at SMP Negeri 7 Denpasar should always increase their motivation to achieve the vision and mission of the SMP Negeri 7 Denpasar institution, provide training to teachers to increase teachers' self-confidence in teaching students, give strict sanctions to teachers who make mistakes, provide motivation to teachers so that later teachers can achieve the targets that have been set.